2021
DOI: 10.1530/edm-20-0097
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypocalcaemia in a COVID-19 female patient

Abstract: Summary Comorbidities are a risk factor for patients with COVID-19 and the mechanisms of disease remain unclear. The aim of this paper is to present a case report of an COVID-19 patient with severe hypocalcaemia. This is a report of an 81-year-old female, suffered from myalgia and fatigue for more than 3–4 weeks. Fever and cough appear 2 days before she presented to the emergency room. On physical examination, she was febrile with a temperature of 38.8°C, accompanied by cough, sore throat, headache, fatigue, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the group of children with pneumonia, 37 (53%) were boys and 33 (47%) were girls, while in the group with ARI, there were 40 (57%) boys and 30 (43%) girls. There were 30 The groups for this study are presented in Table 1. Since the vitamin D deficiency and insufficiency groups were small, they were included in the main group with a low vitamin D content for comparison with the control group with a normal vitamin D content.…”
Section: Resultsmentioning
confidence: 99%
“…In the group of children with pneumonia, 37 (53%) were boys and 33 (47%) were girls, while in the group with ARI, there were 40 (57%) boys and 30 (43%) girls. There were 30 The groups for this study are presented in Table 1. Since the vitamin D deficiency and insufficiency groups were small, they were included in the main group with a low vitamin D content for comparison with the control group with a normal vitamin D content.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Puca et al reported a case of significant hypocalcemia following SARS-CoV-2 in a female case, due to the significant vitamin D deficiency. They concluded a possible association among vitamin D deficiency and the intensity of SARS-CoV-2 (6).…”
Section: Oronavirus Disease 2019 (Covid-19mentioning
confidence: 99%
“…Although SARS-CoV-2 infection is primarily a respiratory disease, it affects various systems and organs throughout the body. Its effects on the respiratory, cardiac, neurological, hematopoietic, gastrointestinal, muscle-skeletal, cutan, ocular, and urological systems are now well known [2][3][4][5][6][7][8][9][10][11][12][13]. In addition to the typical cases, there have been a large number of reports on atypical forms or presentations of the disease and related complications [11,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Its effects on the respiratory, cardiac, neurological, hematopoietic, gastrointestinal, muscle-skeletal, cutan, ocular, and urological systems are now well known [2][3][4][5][6][7][8][9][10][11][12][13]. In addition to the typical cases, there have been a large number of reports on atypical forms or presentations of the disease and related complications [11,[14][15][16][17][18]. However, there are only a limited number of publications on the effect of SARS-CoV-2 infection on the ovaries.…”
Section: Introductionmentioning
confidence: 99%